The wrist joint - Bajuri, M. N. (Springer Verlag, 2013)
In this chapter, information on the wrist anatomy, kinematics and its mechanical behaviours is presented. It commences with a brief explanation on the complexity of the joint, which covers the structure of its hard and soft tissues. All the eight bones constructing the joint were categorized into several groups according to their respective positions. The associated tendons together with five main muscles were well identified in the literature, and thus sufficiently presented in this chapter. This complex joint with numerous articulations appears with many articular cartilages, thus the function are thoroughly explained in this chapter. Further details are presented in the following subsections, which cover description on the structure of each bone, the elements constructing the articular cartilage together with the associated pathology condition and the ligamentous structure. All of these components are essential to bring functions to the joint, allowing its mobility and sustainability. Information on the kinematics of the joint is presented in the last sub-section. This chapter provides sufficient information to assist understanding for the subsequent chapters.